The Application of Tera Exercises in Reducing Levels of Gout Pain in the Elderly - Witriyani Witriyani (Indonesian Journal of Global Health Research, 2025)
Gout is a disease caused by the accumulation of uric acid crystals in the body. In the elderly, cells decline due to the aging process which can cause various diseases, one of which is an increase in uric acid levels (hyperuricemia). Elderly people who suffer from gout experience metabolic imbalances in the body. This disorder causes the formation of monosodium urate crystals which cause inflammation and pain. Exercise, one of which is tera exercise, is a non-pharmacological therapy that aims to reduce pain. Objective: This research is to determine the effect of tera exercise on reducing the level of gout pain in the elderly. Method: This type of research is experimental research with design quasy experiment (nonequivalent control group design). The population in this study were elderly people who attended posbindu in Karanganom. The sampling technique was purposive sampling with a total sample of 26 people. The data in this study was collected using a research instrument in the form of a NRS (Numeric Rating Scale) questionnaire pain scale assessment sheet. The data obtained were analyzed using a non-parametric test with the Wilcoxon test to compare the same subjects before and after being given the intervention. Results: The results of statistical tests using the Wilcoxon test showed that the value was p (0.001) <α (0.005) where the p-value was smaller than the alpha value and Ha was accepted. Conclusion: Based on the research results, it was concluded that there was an effect of applying tera exercise in reducing the level of gout pain in the elderly at Posbindu Karanganom.